Eket Audience Perception of ‘Ekid Idediongo’ Radio Programme on Heritage FM as a Tool for Rural Development - Udoudom, Uduak Imoh; Pam, Christiana Chundung; Aondowase, Saawuan (Darul Yasin Al Sys, 2023)
Recognizing the pivotal role of media in fostering societal progress, this study sought to investigate how the radio programme ‘Ekid Idediongo’ on Heritage radio contribute to the advancement of rural communities in Eket. Through a comprehensive survey method, data was collected from quantitative sources. A survey questionnaire was administered to a diverse sample of 400 respondents within Eket LGA, encompassing various demographic backgrounds. Findings from the study indicated a generally positive perception of the